The Effectiveness of HPV Vaccine in Cervical Cancer Prevention: A Literature Review - juandi, rahma khaerussifa; Pujiastuti, Agustina Tri (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Cervical cancer is one of the leading causes of death in women worldwide, with more than 600,000 cases and 342,000 deaths occurring in 2020. The World Health Organization (WHO) has set a global strategy to eliminate cervical cancer by 2030, where Human Papillomavirus (HPV) vaccination is one of its main pillars. In Indonesia, the HPV vaccination program has been implemented as a preventive measure in preventing cervical cancer, with the main target being girls aged 9 to 14 years. HPV vaccines, especially types 16 and 18, have been shown to be effective in preventing more than 70% of cervical cancer cases. This literature review evaluates the effectiveness of the HPV vaccine in girls in Indonesia and the challenges in its implementation. Although the national vaccination program has been successfully implemented in various regions, challenges such as socio-economic, myths about vaccines, and rejection from parents are still obstacles in achieving optimal vaccination coverage. Continuous education to the public is essential to build a better understanding of the benefits of HPV vaccination in preventing cervical cancer. With higher vaccination coverage, it is hoped that the incidence rate of cervical cancer can be significantly reduced in the future.